Use of the forgotten joint score (FJS)-12 to evaluate knee awareness after quadriceps tendon reconstruction - Manuel P. Sava; Benjamin L. Schelker; Zainab A. Khan; Felix Amsler; Michael T. Hirschmann (BMC Musculoskeletal Disorders, 2023)
Abstract Background Quadriceps tendon rupture (QTR) is a severe injury of the knee extensor apparatus. The study aims to validate the use of forgotten joint score (FJS-12) for functional outcome assessing after surgical treatment of QTR. Methods Fifty-seven patients who underwent surgery for QTR with transosseous suture reconstruction in a single orthopaedic surgery and traumatology center between 2015 and 2020 were eligible for enrolment in this retrospective case series. The demographic data and other pre-operative details such as age, gender, comorbidities and medication use also were extracted from the medical records. Patient reported outcome measures (PROMs) were gathered in the form of Western Ontario and McMaster Universities Arthritis Index Score (WOMAC), Tegner Activity Score (TAS), Lysholm Score and FJS-12 at a mean follow-up time of 49.84 months ± 20.64 months. The FJS-12 was validated by correlation with WOMAC, TAS and Lysholm Score. Results The mean age of all patients were 69.2 ± 13.6 years with 51 (89.5%) males and 6 (10.5%) females. The mean time from injury to surgery was 3.39 ± 5.46 days. All patients reported satisfactory functional outcomes after surgery on FJS-12, WOMAC and Lysholm scores, except the TAS, which decreased slightly from pre-operative level. There was a high negative correlation between WOMAC and FJS-12, but moderate positive correlations between FJS-12 and TAS and Lysholm scores. The Cronbach’s alpha value was 0.96 for 12 items in FJS-12. Conclusion This study has found that FJS-12 is a reliable and easy to assess tool for functional outcomes after QTR reconstruction. It has shown moderate to strong correlation with other commonly used outcome measures (WOMAC, TAS and Lysholm).